Esophageal cancer statistics in China, 2011: Estimates based on 177 cancer registries. Issue 2 (7th December 2015) - Zeng, Hongmei; Zheng, Rongshou; Zhang, Siwei; Zuo, Tingting; Xia, Changfa; Zou, Xiaonong; Chen, Wanqing
Abstract: Background: Esophageal cancer has been a common cancer in China for many years. Using the most recent data collected from the National Central Cancer Registry, we present estimates of the esophageal cancer burden in China in 2011. Methods: Age‐specific incidence and mortality rates by gender and area for 18 age groups were calculated based on data from 177 qualified population‐based cancer registries. The number of new cases of esophageal cancer and cancer deaths were computed by multiplying these rates by the 2011 population. Crude incidence and mortality rates of esophageal cancer were estimated. Results: The estimated number of new esophageal cancer cases and deaths were 291 238 and 218 957, respectively. The crude incidence and mortality rates for esophageal cancer were 21.62/100 000 and 16.25/100 000, respectively. The age‐standardized incidence and mortality rates by world population were 15.83/100 000 and 11.62/100 000, respectively. Both the incidence and mortality rates of esophageal cancer were higher in rural areas than in urban areas, and in men than in women. The age‐specific esophageal cancer incidence and mortality rates increased with age. In China, squamous cell cancer was the most common pathological type of the disease. Conclusion: Esophageal cancer remains a major public health issue in China. Primary and secondary prevention are essential for disease control.